Features, risk factors, and outcomes of older internal medicine patients triggering a medical emergency team call. Issue 3 (14th December 2021) - Wijesundera, Piyumi; See, Emily J.; Robbins, Raymond; Crosthwaite, Amy; Smallwood, David; Jones, Daryl; Bellomo, Rinaldo
Abstract: Background: Information about the epidemiology of older Internal Medicine patients receiving medical emergency team (MET) calls is limited. We assessed the prevalence, characteristics, risk factors, and outcomes of this vulnerable group. Methods: Internal Medicine patients aged >75 years who were admitted via the Emergency Department to a tertiary hospital between January 2015 to December 2018 and who activated a MET call were compared to patients without MET call activation during the same time period. Outcome measures included management post‐MET call, Intensive Care Unit (ICU) admission rates, discharge disposition, length of hospital stays (LOS), and in‐patient mortality. Results: There were 10, 803 Internal Medical admissions involving 10, 423 patients; median age 85 (IQR 81–89) years. Of these, 995 (10%) patients received at least one MET call. MET call patients had greater physiological instability in the Emergency Department and higher median Charlson comorbidity index values (2, IQR 1–3 vs. 1, IQR 0–2; p < .0001) than non‐MET call patients. Overall, 10% of MET call patients were admitted to ICU. MET patients had a longer median length of stay (9 [IQR 5–14] vs. 4 days [IQR 2–7]; p < .001) and higher in‐hospital mortality (29% vs. 7%; p < .001). However, mortality of MET call patients without treatment limitations was 48/357 (13%). Conclusion: One in ten Internal Medicine patients aged >75 years and admitted via ED had a MET call. Physiological instability in ED and comorbidities were key risk factors. Mortality in MET patients approached 30%. These data can help predict at‐risk patients for improving goals of care and pre‐MET interventions.